The Purpose of Law in the Study of Legal Philosophy - H. B. Syafuri; Muhamad Wahyudin (PT FORMOSA CENDEKIA GLOBAL, 2022)
The study of legal philosophy has developed quite rapidly in this country. Because the existence of law as a controller of the state system has a strategic role in realizing prosperity, justice and welfare which should be accessible to every citizen without exception. An equally important discussion regarding the study of legal philosophy is related to the function of law itself in the life of the state, nation and state. This is due to the strategic position of law as a standard rule in the state, and it is even confirmed that in all parts of the world, there is not a single country that does not use law in carrying out its system and state administration. Thus, the study of the function of law with the analysis of legal philosophy is very much needed as a scientific effort to know the essence of the purpose of law, both its function in the state, nation and society